Philosophy as integration in science and islamic education - Nur Arief Hidayatullah; Irawan; Aan Hasanah; Zainal Arifin (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2024)
Studying something using knowledge essentially constitutes one of humanity's efforts to obtain truth. Truth itself is a state that corresponds to the actual object, so studying something through philosophical knowledge is a step towards acquiring true and objective knowledge. This research aims to understand the nature of philosophy as a unifier of science and education.  In this study, the research methodology involves a comprehensive literature review combined with qualitative research methods. The literature review will critically analyze existing philosophical literature to explore the interconnectedness of philosophy, science, and education. Additionally, qualitative research methods such as in-depth interviews, observations, and content analysis will be employed to delve into the perspectives and experiences of experts in the field. Through this combined approach, a deeper understanding of the essence of philosophy as a unifying force in science and education will be achieved. Truth is the essence of philosophy, serving as the foundation for every branch of knowledge. Science, or natural sciences encompassing physics, chemistry, biology, employs scientific methods, scientific thinking, and scientific frameworks.